The dual role of type I interferons in bacterial infections: from immune defense to pathogenesis - Mingjie Qiu; Jiayang Li; Wenqi Wu; Jianan Ren; Xiuwen Wu (mBio)
ABSTRACT Type I interferons (IFNs) are crucial components of the human immune system, playing a key role in regulating immune activity. Existing literature has characterized their antiviral and proviral roles in viral contexts. Type I IFNs also exhibit a dual role in bacterial infections, functioning as defenders or disruptors or both based on factors including but not limited to such things as the bacterial species, infection stage, host immune status, and the route and site of infection. This review provides a summary of the signaling pathways associated with type I IFN responses and discusses the complex mechanisms of type I IFNs in bacterial infections. Because type I IFNs provide an important opportunity to develop personalized treatment strategies, which are expected to be transformed into efficient adjuvant therapy for specific infectious diseases, we also discuss the potential for targeting type I IFNs for therapeutic interventions.